Karakteristik Kimia dan Sensori Ikan Tongkol Asap Asal Pulau Jemaja, Kabupaten Kepulauan Anambas - Aidil Fadli Ilhamdy; Ismael Marasabessy; R. Marwita Sari Putri; Lily Viruly; Yulia Oktavia; Ersti Yulika Sari; Ginanjar Pratama; Jumsurizal Jumsurizal; Tetty Tetty (Jurnal FishtecH, 2022)
The Anambas Islands have many unique traditional products derived from marine products. One of the famous traditional products is smoked tuna. This study aims to determine the chemical characteristics of smoked tuna processed by smoked fish craftsmen on Jemaja Island, Anambas Islands Regency. This research was divided into three stages, identifying the type of raw materials used, sensory analysis, and proximate analysis. The raw material for smoked tuna is known to come from two types of fish, namely Auxis thazard and Thunnus tonggol. The sensory analysis results with the parameters of appearance, aroma, taste, and texture of smoked tuna from the two raw materials were not significantly different for all parameters. These results are the same as the proximate analysis values which consist of testing the water, ash, fat, protein, and carbohydrate content. Based on the overall results of smoked tuna made from Auxis thazard and Thunnus tonggol it is still by the applicable SNI 2725:2013, except moisture content.